Sleep duration and biomarkers of inflammation in African American and white participants with a parental history of Alzheimer's disease. Issue 1 (14th September 2022) - Pak, Victoria M.; Paul, Sudeshna; Swieboda, Dominika; Balthazar, Monique S.; Wharton, Whitney
Abstract: Introduction: African Americans (AA)s have worse inflammation, worse sleep, and a greater incidence of Alzheimer's disease (AD) compared to whites; however, no studies have examined associations between biomarkers, sleep, and cognition, and differences by race. Methods: Seventy‐six cognitively normal, middle aged (45–65 years) adults with a parental history of AD were included in this study. Associations between biomarkers (tumor necrosis factor‐α [TNF‐α], interleukin‐10 [IL‐10], intercellular adhesion molecule‐1 [ICAM‐1], , and C‐reactive protein [CRP]) and self‐reported sleep or cognition measures, were assessed. Results: Average sleep duration was significantly lower for AA versus whites (average[SD]) in hours: 6.02(1.18) versus 7.23(0.91), P = .000004). We found a statistically significant association between plasma IL‐10 and sleep duration (Spearman's ρ = 0.26, P = .04) and CSF ICAM‐1 and sleep quality (Spearman's ρ = 0.30, P = .03). Discussion: Longer sleep duration is positively associated with plasma IL‐10 levels irrespective of race. Sleep quality was positively associated with CSF ICAM‐1 only in African Americans.